Building a working alliance between professionals and service users in family preservation. A multiple case study. Issue 2 (17th October 2017) - Steens, Roos Julie; Hermans, Koen; Van Regenmortel, Tine
Abstract: In the margin of the ongoing experimental and quasi‐experimental research projects on family preservation, some research projects focus on the process through which families accomplish change and acknowledge the importance of the working alliance. There is, however, little information about barriers and facilitators in building this working alliance. To fill this gap, we performed a multiple case study with a triangulation of ethnographical methods such as observation, in‐depth interviews, case file analysis, and multistakeholder focus groups. We illustrate how, in a context of managerialism and transactional leadership, social workers find themselves in a continuous tension between complying with the expectations of their social organization and "tuning in" with the service users. This jeopardizes the working alliance between a social worker and a family. Consequences for research, practice, and policy regarding family preservation interventions are discussed.